Glial‐Neuronal Interactions in Alzheimer's Disease: The Potential Role of a ‘Cytokine Cycle’ in Disease Progression - Griffin, W.S.T. (Brain Pathol, 2006)
The role of glial inflammatory processes in Alzheimer's disease has been highlighted by recent epidemiological work establishing head trauma as an important risk factor, and the use of anti‐inflammatory agents as an important ameliorating factor, in this disease. This review advances the hypothesis that chronic activation of glial inflammatory processes, arising from genetic or environmental insults to neurons and accompanied by chronic elaboration of neuroactive glia‐derived cytokines and other proteins, sets in motion a cytokine cycle of cellular and molecular events with neurodegenerative consequences. In this cycle, interleukin‐1 is a key initiating and coordinating agent. Interleukin‐1 promotes neuronal synthesis and processing of the β‐amyloid precursor protein, thus favoring continuing deposition of β‐amyloid, and activates astrocytes and promotes astrocytic synthesis and release of a number of inflammatory and neuroactive molecules. One of these, S100β, is a neurite growth‐promoting cytokine that stresses neurons through its trophic actions and fosters neuronal cell dysfunction and death by raising intraneuronal free calcium concentrations. Neuronal injury arising from these cytokine‐induced neuronal insults can activate microglia with further overexpression of interleukin‐1, thus producing feedback amplification and self‐propagation of this cytokine cycle. Additional feedback amplification is provided through other elements of the cycle. Chronic propagation of this cytokine cycle represents a possible mechanism for progression of neurodegenerative changes culminating in Alzheimer's disease.